Effects of levo-carnitine in infertile men with asthenozoospermia: a randomized placebo-controlled trial - Al Tarique, Mostafa M.; Banu, Jesmine; Lasker, Nastaran; Munira, S. M.; Anwary, Shahin Ara; Ghosh, Tandra; Sultana, Sharmin; Laila, Rawnok; Akter, Asma; Begum, Makshoda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility is defined as the inability of a sexually active couple to conceive within one year of regular unprotected coitus. Worldwide, it is estimated that 15% of couples are infertile; among them, the male factor is responsible for 50% of cases. This may be the sole underlying cause or a contributory factor to infertility. We aimed to assess the effects of a complementary treatment with a strong antioxidant (levo-carnitine) on sperm function and fertility of infertile men. Methods: This was a randomized controlled trial study and was conducted in the department of reproductive endocrinology and infertility, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh. during the period from July 2022 to June 2023. In our study, we included 72 infertile men presenting with asthenozoospermia. There were two groups-group A (Participants who received tab levo-carnitine 330 mg twice daily orally for three months) and group B (Tab placebo twice daily orally for three months) Result: The majority of patients in both groups, 51% in group A and 49% in group B, were aged 30-40 years, with no significant difference in mean age (35.36±5.50 vs 34.50±5.50, p>0.05). Overall, 62.5% of patients reported primary sub-fertility. Levo-carnitine administration leads to significant improvements in sperm motility (15±2.68 vs. 36.58±5.16, p<0.05). In the case of placebo treatment, there were no significant improvements in sperm motility (13.91±5.53 vs. 16.36±1.19, p>0.05). We found that the comparison of TMC of both groups reflected statistically significant differences (p<0.05) before treatment and after treatment with levo-carnitine and placebo (6.40±2.87 vs 22.91±14.88) 5.64±3.96 vs 7.71±4.91). Conclusions: Levo-carnitine treatment can lead to significant improvements in semen parameters, particularly in motility.